2005
DOI: 10.1103/physrevb.72.024450
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism in hafnium dioxide

Abstract: Thin films of HfO 2 produced by pulsed-laser deposition on sapphire, yttria-stabilized zirconia, or silicon substrates show ferromagnetic magnetization curves with little hysteresis and extrapolated Curie temperatures far in excess of 400 K. The moment does not scale with film thickness, but in terms of substrate area it is typically in the range 150-400 B nm −2 . The magnetization exhibits a remarkable anisotropy, which depends on texture and substrate orientation. Pure HfO 2 powder develops a weak magnetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
296
0
5

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 428 publications
(319 citation statements)
references
References 21 publications
18
296
0
5
Order By: Relevance
“…Difficult issues include the high Curie temperature, [6][7][8][9] the origin of large and anisotropic saturation magnetization in some systems, 7,9 and the specific role of imperfections such as oxygen vacancies, substitutional disorder, and interstitial occupancies. [4][5][6][7]11 These questions have far-reaching ramifications. For example, the anisotropic magnetic moment observed in Co-doped ZnO ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Difficult issues include the high Curie temperature, [6][7][8][9] the origin of large and anisotropic saturation magnetization in some systems, 7,9 and the specific role of imperfections such as oxygen vacancies, substitutional disorder, and interstitial occupancies. [4][5][6][7]11 These questions have far-reaching ramifications. For example, the anisotropic magnetic moment observed in Co-doped ZnO ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…4 Nevertheless, the cationic vacancies induced RTFM order in HfO 2 was later questioned as the diamagnetic HfO 2 powder exhibited weak ferromagnetic order after annealing in vacuum at 750 C for 2 h, which in turn suggested origin of FM to be related to oxygen vacancies. 5 Hong et al 6 observed RTFM in TiO 2 , HfO 2 , and In 2 O 3 , and reported that the annealing of HfO 2 and TiO 2 films in oxygen ambient degraded/destroyed ferromagnetic ordering. They suggested that both oxygen vacancies and confinement effects were key factors in inducing RTFM order.…”
mentioning
confidence: 99%
“…Our findings are consistent with the oxygen vacancies induced RTFM spin-order reported in oxides such as HfO 2 , TiO 2 , and ZnO, etc. 5,6 Fig . 2 shows PL emission spectra of MgO nanocrystallites for the samples calcined for 2 h each at 600 C (in air or oxygen) and 1000 C (in air) recorded with excitation wavelengths of 350 nm.…”
mentioning
confidence: 99%
“…12,13 At higher concentrations, they overlap to form an impurity band which is quite distinct from that formed by any dopants that may be present. The nature of the magnetic coupling of such defects needs to be investigated, especially in view the huge anisotropy of the saturation magnetization in some cases, 5,6,[9][10][11] which points to magnetic moments of largely orbital character. It is worth noting that a huge, strongly-anisotropic susceptibility has been observed for polyalanine molecules absorbed on a gold-plated silicon wafer.…”
mentioning
confidence: 99%